"Cause it's family talking to you": Children acting as change agents for adult food and physical activity behaviors in American Indian households in the Upper Midwestern United States. (August 2015) - Gadhoke, Preety; Christiansen, Karina; Swartz, Jackie; Gittelsohn, Joel
This article presents research findings from the formative phase of OPREVENT, a pilot obesity prevention intervention trial for American Indian households on two reservations in the Upper Midwestern United States. We describe processes by which American Indian children acting as change agents influence adult food and physical activity behaviors on an Ojibwa and a Potawatomi reservation. This study borrows from Bronfenbrenner and Ceci's socio-ecological model and extends Daniel's resiliency theory for practice with vulnerable children. Using purposive sampling, we interviewed 168 community members, including 25 children between 6 and 13 years of age, using adult in-depth and paired-child interviews, household group interviews, focus groups, and community workshops. Results reveal that six American Indian children, 10–13 years old, were acting as change agents. We propose a socio-ecological conceptual framework to guide our understanding and application of a children as change agent approach for adult health behaviors which includes cultural identity (macro-system), institutional and community support (mezzo-system), family support through a secure base (micro-system), and children's sense of belonging, self-esteem, self-efficacy, knowledge, and actions as change agents (intrapersonal factors). Resiliency and vulnerability are dynamic processes that intersect the multiple systems throughout children's developmental stages to bolster their agency. We conclude with considerations for the OPREVENT pilot project and discuss future directions for developing a child as change agent theoretical framework for adult health behavior change.